Zebrafish narrowminded disrupts the transcription factor prdm1 and is required for neural crest and sensory neuron specification - Hernandez-Lagunas, Laura (2005)
Specification of both neural crest cells and Rohon–Beard (RB) sensory neurons involves a complex series of interactions between the neural and non-neural ectoderm. The molecular mechanisms directing this process are not well understood. The zebrafish narrowminded (nrd) mutation is unique, since it is one of two mutations in which defects are observed in both cell populations: it leads to a complete absence of RB neurons and a reduction in neural crest cells and their derivatives. Here, we show that nrd is a mutation in prdm1, a SET/zincfinger domain transcription factor. A Morpholino-mediated depletion of prdm1 phenocopies the nrd mutation, and conversely overexpression of prdm1 mRNA rescues the nrd RB sensory neuron and neural crest phenotype. prdm1 is expressed at the border of the neural plate within the domain where neural crest cells and RB sensory neurons form. Analysis of prdm1 function by overexpression indicates that prdm1 functions to promote the cell fate specification of both neural crest cells and RB sensory neurons, most likely as a downstream effector of the BMP signaling pathway.